2019
DOI: 10.1111/bjd.18333
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis treat to target: defining outcomes in psoriasis using data from a real‐world, population‐based cohort study (the British Association of Dermatologists Biologics and Immunomodulators Register, BADBIR )

Abstract: Background The 'treat to target' paradigm improves outcomes and reduces costs in chronic disease management but is not yet established in psoriasis. Objectives To identify treatment targets in psoriasis using two common measures of disease activity: Psoriasis Area and Severity Index (PASI) and Physician's Global Assessment (PGA). Methods Data from a multicentre longitudinal U.K. cohort of patients with psoriasis receiving systemic or biologic therapies (British Association of Dermatologists Biologics and Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 32 publications
(39 reference statements)
5
112
0
2
Order By: Relevance
“…26 Of interest, a recent study using data from the British Association of Dermatologists Biologics and Immunomodulators Register (BADBIR) suggested an absolute PASI ≤ 2 as a new treatment target; though studies evaluating the proportion of patients achieving this target in longitudinal cohorts are warranted. 27 While comparative effectiveness was not assessed per se in this study, 81% of our cohort were receiving biologics, considered highly effective in psoriasis. The low rates of patients meeting the target in the Corrona Registry may suggest lower efficacy of these therapies in real-world settings compared with that previously seen in randomized clinical trials and other postmarketing studies.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…26 Of interest, a recent study using data from the British Association of Dermatologists Biologics and Immunomodulators Register (BADBIR) suggested an absolute PASI ≤ 2 as a new treatment target; though studies evaluating the proportion of patients achieving this target in longitudinal cohorts are warranted. 27 While comparative effectiveness was not assessed per se in this study, 81% of our cohort were receiving biologics, considered highly effective in psoriasis. The low rates of patients meeting the target in the Corrona Registry may suggest lower efficacy of these therapies in real-world settings compared with that previously seen in randomized clinical trials and other postmarketing studies.…”
Section: Discussionmentioning
confidence: 95%
“…The score ranges from 0 to 30, with higher scores indicating greater effect. 15 Patients were also categorized into 'effect on life' categories based on their DLQI score: none (0-1), small (2-5), moderate (6-10) and very/extremely large (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The EQ-5D-3L measures overall health status based on a visual analogue scale (VAS) from 0 to 100 (higher values indicating better health) and by asking individuals whether they have no problems, some problems, or extreme problems for five dimensions: mobility, self-care, usual activities, pain/discomfort, anxiety/depression.…”
Section: Patient-reported Outcomes Measures (Proms)mentioning
confidence: 99%
“…These studies confirmed secukinumab as an important treatment option for patients with moderate-to-severe plaque psoriasis confirming the solid evidence base established from randomized clinical trials. Nevertheless, greater clinical relevance has been recently attributed to the absolute PASI score compared to the relative PASI score (25)(26)(27)(28). Different absolute PASI scores have been suggested as clinical endpoints, useful to assess clinical response to treatments (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Different absolute PASI scores have been suggested as clinical endpoints, useful to assess clinical response to treatments (27,28). Moreover, absolute PASI values have been identified and increasingly reported as therapeutic targets in a treat-totarget strategy (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation